Lipskynoids A–G, New Acyclic Diterpenes from the Flowers of Carpesium lipskyi. Issue 12 (8th November 2022) - Zhong, Weihong; Li, Min; Gu, Rui; Ding, Rong; Cao, Lan; Mu, Zejing; Du, Xiaolang; Feng, Yulin; Wei, Rongrui; Zhan, Liujuan; Zhong, Guoyue
Abstract: Seven new acyclic diterpenes, namely lipskynoids A–G (1 –7 ), were isolated from the flowers of Carpesium lipskyi, a traditional Tibetan herbal medicine with anti‐inflammatory and antipyretic‐analgesic effects. These new compounds were elucidated by analysis of extensive spectroscopic data including ESI‐MS, 1D, 2D NMR, and DP4+ analyses. Biological assays showed that 1 –7 display significant inhibitory effects against the NO production in LPS‐induced RAW264.7 cells with its IC50 values from 9.9 to 18.47 μM, however, no cytotoxicity effect was observed of these isolates against the growth of HePG2, PC3, DU145, and A549 cells. Abstract :